Does endogenous serum oestrogen play a role in meibomian gland dysfunction in postmenopausal women with dry eye?. Issue 2 (13th April 2016) - Golebiowski, Blanka; Badarudin, Noor; Eden, John; You, Jingjing; Hampel, Ulrike; Stapleton, Fiona
Abstract : Aim: To explore the relationship between serum concentration of sex hormones and dry eye symptoms and signs in postmenopausal women. Methods: A cross-sectional analysis was undertaken. Subjects were 46 postmenopausal women with dry eye (mean age 64.4±5.2 years, 13.7±6.4 years since menopause; not undergoing hormone replacement therapy). Ocular symptoms (Ocular Surface Disease Index (OSDI) and Ocular Comfort Index (OCI)), tear function (tear osmolarity, non-invasive tear break-up time, tear secretion), corneal and conjunctival staining, and meibomian gland (MG) appearance, were recorded. Venous blood was collected and serum concentrations of 17β-oestradiol (E2), 3-α-androstanediol-glucuronide (3α-diol-G), and dehydroepiandrosterone sulfate (DHEA-S) were determined using ELISA. Multiple linear regression analysis was used to examine predictors of dry eye symptoms and signs. Results: Mean serum concentration of E2, 3α-diol-G and DHEA-S was 9.02±13.40 pg/mL, 1.59±1.02 ng/mL and 0.74±0.53 μg/mL, respectively. Ocular symptoms were elevated (mean scores 27.0±18.1 (OSDI) and 40.3±8.4 (OCI)) but signs were within normal ranges. Higher serum E2 concentration along with capped glands, lid telangiectasia and older age was a significant predictor of worse MG secretion quality (p<0.001, R 2 adj=0.75). Serum hormones were not significant predictors of ocular symptoms in multivariate analysis (p>0.05). Conclusion: Serum oestrogen appears to be a key factor in MG signs. Although serum hormone levels did not contribute significantly to dry eye symptoms in this study, it is possible that oestrogen plays a role through its effect on meibum secretion. These findings suggest that MG dysfunction underpins dry eye symptoms in non-Sjögren's dry eye in postmenopausal women. Trial registration number: ACTRN12612000281897.